Epidemiological and secondary ankle stabilizer analysis of professional and amateur field soccer players - Garcia Alloza, Theo; Marion Alloza, Jose Felipe; Kallas Zogaib, Rodrigo; Ejnisman, Benno; Manzini Vieira, Arthur (Journal of the Foot & Ankle, 2026)
Introduction: Football has a high incidence of injuries. The most common injuries are bruises, sprains, and strains, especially to the ankles. Imbalances in muscle strength, motor control, and proprioception, along with prior injuries, increase the risk of new injuries and sprains. The objective of this study is to evaluate and compare epidemiological and performance data from functional tests of professional and amateur soccer athletes at different levels of practice, to identify possible risk and prevention factors for ankle injuries. Methods: Twenty-nine athletes aged 18 to 26 years were divided into two groups (professional and amateur). An epidemiological questionnaire was administered, collecting data on injury history, duration of modality practice, and frequency of physical and technical training in the field, followed by functional tests of single-leg long jump, Side Hop Test, Y Balance test, and objective evaluation of ankle strength using a manual dynamometer. Data were analyzed with descriptive and inferential statistics. Results: A total of 53.3% of amateurs reported previous ankle injury, against only 14.3% of professionals. The professionals, with longer practice time and greater training frequency, also achieved better performance on the unipodal jump, lateral jump, and Y Balance test, especially in the diagonal planes. The strength studied showed a significantly smaller difference in eversion among amateurs. Conclusion: Amateur athletes had a higher history of injuries and muscle imbalances, and lower functional performance, indicating a higher risk of ankle sprain.